Case reportsAdvanced peripheral arterial disease in a 59-year-old man with suspected acute coronary syndrome and normal coronary angiogram - Kręcki, Radosław; D. Kasprzak, Jarosław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Atherosclerosis is a systemic process with variable expression in different vascular beds. Peripheral arterial disease (PAD) is thought to be found in 12% of the age-adjusted population. Reasons for differential anatomic expression of atherosclerosis may involve the interplay between inflammation, shear stresses, flow characteristics, and other local factors. It’s well known that synchronous PAD and coronary artery disease is very common and is likely the result of the systemic impact of atherosclerotic risk factors. On the other hand, there are limited data concerning atherosclerotic process restricted to specific vascular areas in the human body.